2013
DOI: 10.1093/mnras/stt1976
|View full text |Cite
|
Sign up to set email alerts
|

Molecular gas properties of the giant molecular cloud complexes in the arms and inter-arms of the spiral galaxy NGC 6946

Abstract: Combining observations of multiple CO lines with radiative transfer modeling is a very powerful tool to investigate the physical properties of the molecular gas in galaxies. Using new observations as well as literature data, we provide the most complete CO ladders ever generated for eight star-forming regions in the spiral arms and inter-arms of the spiral galaxy NGC 6946, with observations of the CO(1-0), CO(2-1), CO(3-2), CO(4-3), CO(6-5), 13 CO(1-0) and 13 CO(2-1) transitions. For each region, we use the la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…As seen from Figure 7, the ∆χ 2 r contour maps indicate that TK increases sharply at lower n(H2), and it gradually decreases as n(H2) increases (i.e. the banana-shaped degeneracy, see van der Tak et al 2007;Topal et al 2014;Topal 2020). Single Gaussian profiles are seen in the PDFs (see Section 4.2), except that for TK (Fig.…”
Section: Modellingmentioning
confidence: 80%
See 1 more Smart Citation
“…As seen from Figure 7, the ∆χ 2 r contour maps indicate that TK increases sharply at lower n(H2), and it gradually decreases as n(H2) increases (i.e. the banana-shaped degeneracy, see van der Tak et al 2007;Topal et al 2014;Topal 2020). Single Gaussian profiles are seen in the PDFs (see Section 4.2), except that for TK (Fig.…”
Section: Modellingmentioning
confidence: 80%
“…The data for Seyfert galaxies in panel c were taken from Papadopoulos & Seaquist (1998). Black circles with a cross in panels a and d represent the GMCs in NGC 6946 (Topal et al 2014) and in M31 (Brouillet et al 2005), respectively. The light grey shaded areas in panels a and c show the range for the R 11 ratios in spirals (Paglione et al 2001), while the dark grey shaded area in panels a, b and d show the range for R DC ratios in spirals (Gao & Solomon 2004).…”
Section: Line Ratiosmentioning
confidence: 99%
“…As revealed from Figure 5, there is degeneracy in T K due to its characteristic 'banana'-shaped ∆χ 2 r contours or inverse n (H 2 ) − T K relationship ( [25,37]; see also appendix C of [15]). The PDF of the kinetic temperature T K also shows a single-peaked distribution peaked at 20 K where the χ 2 result meets with the peak, followed by a steady decrease.…”
Section: Modeling Resultsmentioning
confidence: 99%
“…We compare our best-fitting results (listed in Table 5) to that of literature studies done for the center and along the disc of one spiral and one ETG using similar lines and the same methods. Molecular gas properties along the disc of the spiral galaxy NGC 6946 and ETG NGC 4710 [25][26][27]37] were also studied using the LVG approximation. We found that n (H 2 ) is to be higher in the center of NGC 2903 compared to that found in most of the regions studied in the arms of NGC 6946 [25] and in the center of NGC 6946 [26,27].…”
Section: Modeling Resultsmentioning
confidence: 99%
See 1 more Smart Citation